Green investment, energy efficiency, and economic growth: does economic freedom matter? Evidence from BRICS countries - Mu, HongMei (Technological and Economic Development of Economy, 2024)
Sustainable development goals, particularly number 7, clearly urges economies over the globe to multiple their efforts in order to improve efficiency. Although witnesses stressed out the importance of energy efficiency and claimed that when it is improved drastically, it triggers economic growth, however, the reported evidences to support the claim are mixed. In BRICS scenario, economies are experiencing the change from high-speed growth to high quality growth, due to which it is equally important to look into green investment as it is an essential tool to build high quality economic growth. Although green investment targets energy conservation as well as ecological deficit as it main goal. However, limited literature claims that it affects economic growth as well. Thus, the present study aims to assess green investment, energy efficiency, and economic growth (EG) and their impact on economic freedom index of the BRICS countries. Methods of Moments-Quantile-Regression (MMQR) approach is applied to explore the association between the understudy constructs in the time span of 2001–2020. Interestingly, it is revealed that green investment, energy efficiency and renewable energy are positively related with economic freedom index of the BRICS countries. With the evidences, the study proposes a conclusive remark to spur development across the countries.